The impact of shared social spaces on the wellness and learning of junior doctors: A scoping review. Issue 4 (23rd October 2022) - Uys, Ciska; Carrieri, Daniele; Mattick, Karen
Abstract: Introduction: Impaired wellness among junior doctors is a significant problem. Connectedness and sense of belonging may be important factors to prevent and reduce mental ill‐health. Shared social spaces in which health care staff can meet informally are thought to improve connectedness; however, these spaces are in decline. It is unclear what is known about such spaces, how they are used, and their impact on wellness and learning. This study aims to identify and synthetise available literature that informs our current understanding of the nature of shared social spaces as an intervention impacting wellness and learning of junior doctors. Methods: A scoping review was conducted following the Arksey and O'Malley five‐step framework. The review question is 'What is the evidence of the impact of shared social spaces on wellness and learning of junior doctors?' We searched five databases: MEDLINE, EMBASE, APA PsychINFO, APA PsychExtra, and ERIC. We conducted thorough supplementary searches in addition to the database search. Results: We included 41 articles. These were predominantly letters, commentaries, and editorials with only five primary research studies. We identified four significant common attributes of shared social spaces, which can be credited with positive impacts on wellness and learning: (1) Informal: fostering connectedness and belonging, trust and teamwork and offering access to informal help and support; (2) safe: allowing reflection, debrief and raising of concerns; (3) functional: there is planning of clinical care activity, sense of control and engagement from users and provision of refreshment; (4) legitimate: regular maintenance and use of shared social spaces affect role modelling, sustainability and wellness culture. Discussion: This review identified several ways in which shared social spaces impact positively on learning and wellness. There is little primary research in this area. Future research would be useful to further examine how and why this works. Abstract : This review identified several ways in which shared social spaces may impact positively on the wellness and learning of junior doctors. Future realist research would be useful to further examine how and why this works.